2019
DOI: 10.20524/aog.2019.0403
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of bezafibrate and ursodeoxycholic acid in patients with primary biliary cholangitis: a meta-analysis of randomized controlled trials

Abstract: Background Ursodeoxycholic acid (UDCA) and obeticholic acid are currently approved treatments for primary biliary cholangitis (PBC). Since some patients do not respond adequately to UDCA, other therapies, such as bezafibrate, have been developed. In this meta-analysis we evaluated the efficacy and safety of using both UDCA and bezafibrate in patients with an inadequate response to UDCA. Methods We evaluated all randomized controlled trials comparing the combination of UDCA and bezafibrate with UDCA monotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Bezafibrate, a drug used to target hypercholesterolemia and hypertriglyceridemia, has also been used to treat PBC in combination with UDCA. 57 , 58 A study of 369 PBC patients showed that UDCA and bezafibrate combination therapy was effective in decreasing liver enzymes in patients non-responsive to UDCA only. 58 Another study was conducted on 22 PBC patients over a 6-month period.…”
Section: Anxiety and Depression - Management And Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bezafibrate, a drug used to target hypercholesterolemia and hypertriglyceridemia, has also been used to treat PBC in combination with UDCA. 57 , 58 A study of 369 PBC patients showed that UDCA and bezafibrate combination therapy was effective in decreasing liver enzymes in patients non-responsive to UDCA only. 58 Another study was conducted on 22 PBC patients over a 6-month period.…”
Section: Anxiety and Depression - Management And Recommendationsmentioning
confidence: 99%
“… 57 , 58 A study of 369 PBC patients showed that UDCA and bezafibrate combination therapy was effective in decreasing liver enzymes in patients non-responsive to UDCA only. 58 Another study was conducted on 22 PBC patients over a 6-month period. Patients taking 600mg/day of UDCA and 400mg/day of bezafibrate had significantly lower ALP levels at the end of treatment.…”
Section: Anxiety and Depression - Management And Recommendationsmentioning
confidence: 99%
“…Ten randomized clinical trials including the BEZURSO trial reported a positive effect of fibrates on cholestasis (116)). In the BEZURSO trial bezafibrate at dose of 400 mg /d improved ALP and bilirubin during a follow up of 2 years and a normalization of ALP and bilirubin was achieved in 31 % of patients vs 0% in the placebo group (117).…”
Section: Ppar Agonistsmentioning
confidence: 99%
“…FGF19 is an endocrine hormone induced in the gut by activation of farnesoid X receptor (FXR), which can inhibit bile acid synthesis through inhibition of CYP7A1 [ 23 ]. Several traditional meta-analyses [ 11 , 14 , 15 ] manifested that fenofibrate and bezafibrate are effective adjunctive therapies in the treatment of primary biliary cirrhosis. some single or combined therapies about obeticholic acid [ 24 26 ], aldafermin [ 27 ], seladelpar [ 28 , 29 ], elafibranor [ 16 ], saroglitazar [ 18 ], and budesonide [ 30 ] in the treatment of UDCA-refractory PBC patients have been studied by randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%